2003
DOI: 10.1128/jcm.41.5.2080-2083.2003
|View full text |Cite
|
Sign up to set email alerts
|

pgi Genotyping Is a Surrogate for Serotyping of Encapsulated Haemophilus influenzae

Abstract: Study of the epidemiology of invasive infections caused by encapsulated Haemophilus influenzae has been complicated by the poor sensitivity and specificity of the serologic assays used to identify specific capsular polysaccharides. The population structure of these bacteria is highly clonal, however, and serotype is highly correlated with other genetic characteristics. We sought to determine if alleles of the highly conserved phosphoglucose isomerase (pgi) gene correspond to the serotypes of encapsulated H. in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
2
3
0
Order By: Relevance
“…The limited genetic diversity of the recent Danish clinical isolates of Hif revealed by our phylogenetic analysis (Fig. 1) is in full agreement with previous observations from the USA (Anyanwu et al, 2003;Omikunle et al, 2002) and Spain (Campos et al, 2003). The close relationship of our isolates to strains representing cases from the USA suggests that these recent cases of Hif disease are caused by a single clone (according to the definition of Maynard Smith, 1995) in which genetic diversity is very limited.…”
Section: Discussionsupporting
confidence: 90%
“…The limited genetic diversity of the recent Danish clinical isolates of Hif revealed by our phylogenetic analysis (Fig. 1) is in full agreement with previous observations from the USA (Anyanwu et al, 2003;Omikunle et al, 2002) and Spain (Campos et al, 2003). The close relationship of our isolates to strains representing cases from the USA suggests that these recent cases of Hif disease are caused by a single clone (according to the definition of Maynard Smith, 1995) in which genetic diversity is very limited.…”
Section: Discussionsupporting
confidence: 90%
“…It cannot be used to distinguish between noncapsulate strains and capsule-deficient mutants of type b strains (b -strains) because some of these bacteria exhibited nonspecific agglutination. This discrepancy may be due to the low specificity of antiserum which results in difficulty in interpreting the agglutination test (Falla et al, 1994;CDC, 2002;Anyanwu et al, 2003). The findings of this study is consistent with previous data.…”
Section: J Microbiolsupporting
confidence: 92%
“…We believe that serotyping should be confirmed by PCR genotyping to minimize the errors of conventional serotyping using the slide agglutination test (CDC, 2002) because PCR sero-genotyping is more sensitive and specific than traditional slide agglutination assays. Nontypeable H.influenzae is also responsible for pediatric pneumonia (Heath et al, 2001;Anyanwu et al, 2003;LaClaire et al, 2003). We found that 77.7% cases occurred under 1 year old.…”
Section: J Microbiolmentioning
confidence: 93%
“…Strains containing capsule-specific genes (region 2) may be phenotypically and serologically nontypeable if critical elements of the gene cluster such as the capsule export gene bexA (region 1) or transport genes hcsA and hcsB (region 3) are missing (18,25,32,43). The nucleotide sequences of the highly conserved housekeeping gene for phosphoglucose isomerase (pgi, one of the seven housekeeping loci used in multilocus sequence typing [MLST]) are conserved within capsule types, and this additional molecular scheme has been suggested as a surrogate for capsule typing (2).…”
mentioning
confidence: 99%